Peranan Badan Pengawas Pemilihan Umum Kabupaten Karawang Dalam Memberikan Pendidikan Politik Kepada Pemilih Disabilitas - Ahmad Fariji; Aris Riswandi Sanusi; Lusiana Rahmatiani (Jurnal Kewarganegaraan, 2024)
The author conducted research examining the role of the Election Supervisory Board of Karawang Regency in providing political education to voters with disabilities. This study applies a qualitative method. The qualitative approach is used to describe and understand the phenomena emerging in the research based on information provided by the research subjects. The subjects of this research are the Chairman of the Karawang Regency Election Supervisory Board (Bawaslu), the Coordinator of the Prevention, Community Participation, and Public Relations Division, and the Coordinator of the Violation Prevention, Data, and Information Division. The findings of the study reveal that the Karawang Regency Election Supervisory Board plays a very important role in the process of political education for individuals with disabilities. Bawaslu Karawang implements a political education concept that focuses on inclusivity and accessibility for people with disabilities. These efforts include providing educational materials in accessible formats and collaborating with the General Election Commission (KPU) to ensure that polling stations (TPS) are disability-friendly. Political education is tailored to meet the specific needs of individuals with disabilities, ensuring that they understand their rights and how to participate in elections. Participatory supervision involves individuals with disabilities in the election monitoring process, giving them direct insight into the electoral mechanisms and the importance of each stage in maintaining fairness and transparency. This also helps them understand their rights and responsibilities as voters, as well as how to report violations. Keywords: Bawaslu’s Role, Political Education, Disability